Students' Nine Motivation in Attending Program of Quran Memorization - Japeri Japeri; Mona Lisa; Maradona Maradona; Syamsuardi Syamsuardi; Mulia Siddiq (International Journal of Multidisciplinary Research of Higher Education, 2023)
This study aims to describe the real motivation of students to join the program tahfidz at the Sakinah Quran House. This study used a qualitative method with a phenomenological approach. Data sources were taken from ten informants through an interview protocol. All interview results were then analyzed thematically using the NVivo 12 qualitative analysis software. Overall, the findings showed nine students' motivation to join the program. tahfidz.The nine motivations are: i) Reaching the blessing of Allah SWT through the Quran, ii) Wanting to be closer to the Quran, iii) being Interested in the beauty of the verses of the Quran, iv) Having the opportunity to help parents in the afterlife, v) Wanting to bring the memorization of the Quran before Allah SWT in the afterlife, vi) Want to pass on tahfidz beforehand, vii) There is encouragement from the family, viii) The environment, and ix) The course major that is occupied. The results of this study can be used as initial data for future researchers in examining different issues related to this problem and various other issues that are relevant to this context.